THE IMPORTANCE OF SKILLS FORMATION IN MATHEMATICS LESSONS - Talipova, М.Ж.; Bekbauova, А.У. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Kazakhstan in the era of the fourth technological revolution: rapid development of information technologies, introduction of process of distance education in context of global pandemic, make significant changes in education system. Purpose of education is not only formation of knowledge and skills of the student, but also development of competencies aimed at mastering the program of basic vocational education and application of these knowledge and skills in everyday life. Article considers the importance of formation and development of information, communicative, problematic and self-management skills of student in mathematics using new teaching methods. Effectiveness of Stem, Clil technology was indicated, which are new methods in mathematical education, questionnaire was analyzed, conducted to determine the importance and problems in the integrated lesson, dictionary of mathematical terms was compiled when using Clil and Stem learning scheme was created, and draft of questions reflecting an interdisciplinary relationship on the topic "differential equations" was proposed.